2007
DOI: 10.1634/stemcells.2006-0505
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2-Derived Prostaglandin E2 Protects Mouse Embryonic Stem Cells from Apoptosis

Abstract: Little is known about prostaglandin synthesis and function in embryonic stem cells. We postulated that mouse embryonic stem (mES) cells possess enzymes to synthesize protective prostaglandins. Compared with differentiated adult cells, mES cells were less susceptible to H 2 O 2 -induced apoptosis. However, their apoptosis was enhanced by indomethacin or SC-236, a selective inhibitor of cyclooxygenase (COX)-2. Analysis of COX pathway enzymes by Western blotting revealed expression of COX-2 and cytosolic and micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 42 publications
(48 reference statements)
4
59
1
2
Order By: Relevance
“…PGE 2 was found to have a positive affect on the growth of hematopoietic stem cell progenitors obtained from zebrafish and mouse embryonic stem cells [84]. PTGS2 activity and PGE 2 have also been associated with mouse embryonic stem cell proliferation [85][86][87] and prevention of apoptosis [88]. These data are in agreement with our findings of increased PTGS2 activity and PGE 2 secretion in cells that are supportive of hESC growth.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…PGE 2 was found to have a positive affect on the growth of hematopoietic stem cell progenitors obtained from zebrafish and mouse embryonic stem cells [84]. PTGS2 activity and PGE 2 have also been associated with mouse embryonic stem cell proliferation [85][86][87] and prevention of apoptosis [88]. These data are in agreement with our findings of increased PTGS2 activity and PGE 2 secretion in cells that are supportive of hESC growth.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we also detected high expression of PGIS in cells that were supportive of hESC growth and found significantly higher concentrations of 6-k-PGF 1a in hESC supportive CM than in nonsupportive CM. In a study on mouse embryonic stem cells, however, no PGIS was detected in the cell lysate and no 6-k-PGF 1a was detected in the CM of undifferentiated cells [88]. Increased levels of PGI 2 have also recently been associated with inducing hESC to form cardiomyocytes [89], indicating varying roles for PGI 2 depending on the species and specific microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, several hundreds of genes showed changed expression in the tumor tissues from the EP2-knockout mice compared with tumor tissues from the wild-type mice. A reason for this could be that EP2 signaling in host tissues is involved in several different pathways that are important events in tumor cells associated with tumor progression, including angiogenesis, the upregulation of COX-2, the loss of E-cadherin expression and anti-apoptosis in stem cells (16,22,(25)(26)(27)(28). Prom-1, also known as CD133, and CD44 are well-known markers of cancer stem cells, indicating reduced gene expression in the tumor tissues from the EP2-knockout mice in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandin-endoperoxide synthase 2 (PTGS2) is critical for germ cell maturation and somatic-germ cell interactions in the mammalian gonad both in vivo and in vitro (Neal et al 1975, Takahashi et al 2006, Winnall et al 2007. Recent evidence suggests that this multifunctional enzyme is also responsible for protecting mouse embryonic stem cells and renal interstitial cells from oxidative stress and hypertonicity-induced apoptosis (Moeckel et al 2003, Liou et al 2007); thus, we evaluated the mRNA expression of PTGS2 in response to VEGF treatment. In respect to the 0-h time point, VEGF treatment significantly induced the expression of PTGS2 in bovine testis tissue at 3 h, 6 h (P!0.001), and 24 h (P!0.01) when compared with controls ( Fig.…”
Section: Quantitative Real-time Rt-pcr Analysis Of Genes Regulated Bymentioning
confidence: 99%